PENGGUNAAN EJAAN PADA RUANG PUBLIK DI KOTA MERAUKE - Siswanto NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This paper aims to describe the forms of spelling errors in the public space in Merauke city. This research is a qualitative descriptive study of language error analysis. The population includes all of usage of spelling in public spaces in Merauke city. Population samples are selected purposively. Data is collected by photo documentation and observation. The results show some spelling errors in public space in the town of Merauke, including capitalization errors, spelling errors, punctuation errors, and errors due to the use of foreign terms.